Tools for Practical Software Verification International Summer School, LASER 2011, Elba Island, Italy, Revised Tutorial Lectures - Meyer, Bertrand; Nordio, Martin (Programming and Software Engineering, 2012)
The LASER school is intended for professionals from the industry (engineers and managers) as well as university researchers, including PhD students. Participants learn about the most important software technology advances from the pioneers in the field. The school's focus is applied, although theory is welcome to establish solid foundations. The format of the school favors extensive interaction between participants and speakers. LASER 2011 is devoted to software verification tools. There have been great advances in the field of software verification in recent years. Today verification tools are being increasingly used not only by researchers, but by programming practitioners. The summer school will focus on several of the most prominent and practical of such tools from different areas of software verification (such as formal proofs, testing and model checking). During the school the participants will not only learn the principles behind the tools, but also get hands-on experience, trying the tools on real programs.